KONSEP KELUARGA DALAM SUNNAH NABI - Anis Hidayatul Imtihanah (Al Hikmah: Jurnal Studi Keislaman, 2016)
Generally, when we discussed about family there are two types of family, nuclear and extended family. But in the sunna there is no clear definition that explain about family. There are many words of  “أهل” in the sunna, that referred to the family, relative, kinship and wife. Based on the variety meaning of “ahl / أهل” word, I can conclude that family concept in the sunna is the collaboration or the fusion between nuclear and extended family. It is also showed about the flexibility in Islam for people in deciding family concept, whether nuclear or extended family.